KUALITAS AIR SUNGAI BELAWAN KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA The Belawan River Water Quality in District Pancur Batu Deli Serdang Regency of North Sumatera - Uzi Zefanya Gulo; Ternala Alexander Barus; Ani Suryanti (AQUACOASTMARINE, 2015)
Belawan River waters are widely used for a variety of community activities. Theexistence of community activities into the waters of the rivers affecting water quality inBelawan River Pancur Batu subdistrict. This study aims to determine the water quality basedon physical and chemical parameters as a result of community activities in Belawan RiverPancur Belawan Subdistrict of Deli Serdang Regency. Physical and chemical parameters ofwater were analyzed with method Storet. The study was conducted in March and April 2015.The method used is purposive random sampling. Stations used consisted of stationI (Without Activity), station II (Dredging Sand), and the station III (Recreation and MCK).The value of physical and chemical parameters of water include temperature from 25.00 to27.00 ° C, turbidity (TSS) from 22.68 to 28.86 mg / l, TDS 156.6 to 187.2 mg / l, DO 4.80 -6.00 mg / l, pH 7.20 to 8.10, BOD 1.20 to 2.20 mg / l, nitrate 0.812 to 1.123 mg / l, phosphatefrom 0.112 to 0.153 mg / l, the organic content of the substrate from 0.372 to 0.705 %. Basedon the physical and chemical parameters of water, the station I and II meet the water qualitystandard Class II (lightly polluted), whereas the third station meet Class II water qualitystandard (not being).Keywords: water quality, society activities, belawan river